METHODOLOGY FOR APPLYING MODERN TECHNOLOGIES FOR ASSESSING THE QUALITY OF EDUCATION IN MATH - Yunusova Gulnoza Abduxalikovna (Web of Journals Publishing, 2024)
This article considered about testing, a rating system and educational portfolios, which can be used as innovative tools in assessing the quality of educational results and it is discussed about their pluses and drawbacks.
Keywords: system, knowledge, process, quality, education, learners, teacher, result, test, skills, competencies.